Levantamento cariotípico em espécies de peixes marinhos costeiros de fundo arenoso (Osteichthypes, Perciformes) - Accioly, Ingrid Vilar (2007)
Cytogenetics analyses in fish are important because they compose a private group among the vertebrates, occupying a central position in the animal evolution. The Perciforms Order, dominant in the marine and freshwater environment, it constitutes a model potentially useful in the genetic evaluation of populations, as well as in the understanding of its evolutionary processes. In spite of this, cytogenetics studies in this great group is scarce, above all for the inhabitants of sandy bottom and pelagics habits. The present work proposed to contribute for the cytogenetic characterization of nine species of fish marine of sandy bottom of the coast of Rio Grande do Norte (Brazil), identifying the evolutionary patterns related to the karyotype in these species and the existence of filogenetics affinities between them and other Perciformes. The animals were collected in the beaches of the Redinha, Ponta Negra and Búzios (Coast of Rio Grande do Norte) and in Saint Peter and Saint Paul Archipelago. Later on they were submitted to the cytogenetics technical that consist of mitotic estimulation, obtaining of mitotics chromosomes, proceeded by techniques of conventional coloration (Giemsa) and chromosomic bands (Ag-RONs and C band). Diploid number and fundamental number equal to 48 were observed in most of the species: Menticirrhus americanus, Ophioscion punctatissimus, Pareques acuminatus (Sciaenidae); Chloroscombrus chrysurus (Carangidae); Echeneis sp. 2 (Echeneidae); Archosargus probatocephalus (Sparidae) and Orthopristis ruber (Haemulidae). Trachinotus goodei (NF=52) (Carangidae) and Echeneis sp. 1 (Echeneidae) (NF=54) presented variation in NF, staying constant a diploid number equal to 48. RONs was situated in pericentromeric position in whole the scianids, and in the species Echeneis sp. 2 (22° pair), O. ruber and A. probatocephalus (1° pair), coinciding with great heterocromatics blocks in M. americanus (1° pair), P. acuminatus (2° pairl) and O. ruber (1° pair). RONs was also located in the telomeric area of the short arm of the 5° and 11° acrocentrics pairs in T. goodei, 4° and 19° pairs of C. chrysurus, 1° pair (sm) of Echeneis sp. 1. The C band detected centromeric blocks in most of the chromosomes of the species of Sciaenidae, Carangidae and Echeneidae, with great blocks in A. probatocephalus (4° pair). Heterocromatic blocks in telomeric areas in submetacentrics of Echeneis sp. 1, and pericentromerics in M. americanus (1° and 8° pairs), O. punctatissimus (1° pair) and P. acuminatus (2° pair) were also observed. It is noticed a marked conservatism cromossomic in the species of the family Scianidae and Haemulidae in what says respect to the number of acrocentrics chromosomes and the location of RONs. Even so it is outstanding the presence of heterocromatinization events during the karyotypic evolution of this family. Already in the families Sparidae and Carangidae, the obtained results reaffirm examples of small variations structural resultants of inversion and translocation Robertsonian, as important mechanisms of diversification karyotipical, as well as a pattern numerical evolutionary conserved, also observed in representatives of Echeneidae of Atlantic in relation to Pacific. The presence of RONs multiple, observed in the species T. goodei and C. chrysurus seems to represent a character derived in the family Carangidae. The results for the species O. ruber and A. probatocephalus suggest the presence of possible geographical or climatic barriers among populations of NE of Brazil in relationship the one of the SE